Retreat patterns and dynamics of the Sentralbankrenna glacial system, central Barents Sea - Esteves, Mariana da Silveira Ramos; Bjarnadóttir, Lilja Rún; Winsborrow, Monica; Shackleton, Calvin; Andreassen, Karin (Quaternary Science Reviews, 2017)
The Barents Sea Ice Sheet (BSIS) is a good palaeo-analogue for the present day West Antarctic Ice Sheet. Both were marine-based ice sheets, particularly vulnerable to ocean warming and sea-level rise. Understanding the BSIS ice dynamics and patterns of retreat since the Last Glacial Maximum (LGM) is useful in developing our knowledge of spatial and temporal variations during marine-based ice sheet retreat. While the western margins of the Barents Sea have been extensively studied, few studies have focused on the central regions, which hosted key ice stream tributaries and major ice domes and divides. Presenting a new high-resolution (5 m) bathymetric dataset, this glacial geomorphological study focuses on the Sentralbankrenna palaeo-glacial system in the central Barents Sea. A large number of grounding zone wedges, mega-scale glacial lineations and areas with tunnel valleys and palaeo-subglacial basins were identified. These form the basis for a six-stage reconstruction of ice stream retreat through deglaciation since the LGM. In reconstructing the retreat of the Sentralbankrenna Ice Stream, we document the rapid but highly spatially variable pattern of retreat of a marine-based ice sheet margin. The presence of several tunnel valleys and interconnected palaeo-subglacial basin systems indicates an abundance of meltwater, likely to have been stored and released through several discharge events, significantly influencing the ice stream margin dynamics. This study provides insight into the behaviour and dynamics of ice during the late stages of the BSIS deglaciation within the central Barents Sea, increasing our understanding of grounding line processes.